An Optimum Switch from Double-Declining Balance to Sum-of-the-Years Digits Depreciation. - Sunley, Emil M. (The Accounting Review, 1971)
The article focuses on an optimum switch from double declining balance to sum-of-the-years digits depreciation. Economists Bernhard Schwab and Robert E.G. Nicol developed this optimum switching rule. Such a switch in the method of tax depreciation was made available by the issuance of Revenue Procedure 67-40, effective October 23, 1967. Schwab and Nicol demonstrated that the present value of the tax savings can be increased by a timely switch from double-declining balance to sum-of-the-years digits depreciation. The optimum year to switch depends on the useful life of the asset, the salvage value taken into account for tax purposes, and the discount rate. This paper simplifies the mathematics presented by Schwab and Nicol, corrects and extends the results, and indicates the percentage increase in the present value of the tax savings which may be obtained by a timely change in the method of depreciation. The Internal Revenue Code authorizes the straight-line, the double-declining balance, and the sum-of-the-year digits methods of depreciation. Under the straight-line method, the depreciable basis is distributed evenly over the life of the asset.